Upaya Pembangunan Program Pendidikan Luar Sekolah - Salsa Shabilla Putri; Dinia Nikmatus Sholicha; Wahyu Fitriya; Balqis Ersa Andriana; Aprilia Rofiana Sari; Nuzulul Fatimah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
There have been several articles written covering the theme of human capital development in out-of-school education programs. Currently, the quality of investment in the value of education and human capital is very interesting to study. In order to know what can be done so as to develop and create human resources that are more productive efficient, confident, and competitive in the global context.